New toxodontid (Notoungulata) from the Early Miocene of Mendoza, Argentina - Forasiepi, Analía M. (2015)
We describe a new toxodontid species, Nesodon taweretus sp. nov., from the Aisol Formation in Mendoza Province, central-west Argentina. Nesodon is a frequently found Toxodontidae, member of the Notoungulata, an extinct endemic group of Cenozoic South American mammals that are ecologically similar to current hoofed ungulates. The holotype of N. taweretus sp. nov. is a skull, and we tentatively assign some mandibular fragments and postcranial bones. N. taweretus sp. nov. differs from the other Nesodon species in several cranial and dental features, and close comparisons were made with the Patagonian Nesodon imbricatus, common in the Santa Cruz Formation (Santacrucian Age, Early Miocene). The material is of a similar size to N. imbricatus, with a body mass estimation of about 550 kg. The phylogenetic analysis groups N. taweretus sp. nov. with other species of Nesodon. The absolute age of the Aisol Formation has been established at ca 19.480 ± 0.025 Ma (Burdigalian; Early Miocene) by means of U–Pb zircon dating. The vertebrate association is encompassed by the Santacrucian Age. Latitudinal separation between Mendoza and Patagonia in the south would have favored taxonomic differences, as reflected in the species of Nesodon.